2019
DOI: 10.1177/0885328219835995
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory and antimicrobial activity of bioactive hydroxyapatite/silver nanocomposites

Abstract: Biomaterials are often used in orthopedic surgery like cavity fillings. However, related complications often require long-term systemic antibiotics, device removal, and extended rehabilitation. Hydroxyapatite/silver (HA/Ag) composites have been proposed as implantation biomaterials owing to the osteogenic properties of hydroxyapatite and to the antimicrobial efficiency of silver. Nevertheless, higher silver concentrations induce cytotoxic effects. The aim of this study was to synthesize and characterize HA/Ag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Also, the increase in oxidative stress promotes the syntheses of pro-inflammatory molecules (IL-1, IL-6 and TNF-α) which trigger bone damage and enhance osteoclastic activity, thus disturbing the bone remodelling balance [108]. It has been reported that silver hydroxyapatite nanoparticles attenuate the inflammatory effect by decreasing the syntheses of the pro-inflammatory mediators like TNF-α and IL-1 [109]. Nakayama et al [110] found that TNF-α stimulated BSP mRNA expression at three hours of incubation with Saos2 osteoblast-like cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the increase in oxidative stress promotes the syntheses of pro-inflammatory molecules (IL-1, IL-6 and TNF-α) which trigger bone damage and enhance osteoclastic activity, thus disturbing the bone remodelling balance [108]. It has been reported that silver hydroxyapatite nanoparticles attenuate the inflammatory effect by decreasing the syntheses of the pro-inflammatory mediators like TNF-α and IL-1 [109]. Nakayama et al [110] found that TNF-α stimulated BSP mRNA expression at three hours of incubation with Saos2 osteoblast-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in the current work, the femur bone from osteoporotic rats administered nAg/HA showed a higher intensity of colour representing the alizarin red S staining in comparison with the osteoporotic rats. Martínez-Sanmiguel et al [109] stated that silver/hydroxyapatite nanoparticles have the ability to promote mineralisation/apatite nucleation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Silver has well-documented antibacterial activity. However, the bactericidal properties of silver-doped apatites are still tested to find the best structure . Thus, the antibacterial activity of fluor- and hydroxyapatites doped with Ag + (1.0, 2.5, and 5.0 mol%) was investigated using bacterial strains commonly applied for drug susceptibility testing.…”
Section: Resultsmentioning
confidence: 99%
“…48 The results also showed good antibacterial activity against P. aeruginosa and E. coli, which is consistent with the previous findings. 47,49 3.7. Antibiofilm Activity.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 99%
“…As demonstrated in previous studies, which used a combination of HA and silver to reduce the release of nitric oxide and decrease the secretion of IL-1 and TNF-α in cells that were stimulated with Lipopolysaccharide (LPS), LPS stimulates monocytes/ macrophages through TLR4, resulting in the activation of a series of signalling events that potentiate the production of inflammatory mediators. 22,23 There is a correlation between the particle size of HA and the secretion of TNF-α. A previous study showed that a smaller HA particle size (especially a diameter of 1-2 µm and a pore size of 10-50Å) stimulates a higher macrophage TNF-α secretion.…”
Section: Discussionmentioning
confidence: 99%